Dissipative output feedback tracking control of Markov jump systems under compensation scheme. (December 2022) - Xue, Min; Yan, Huaicheng; Zhang, Hao; Wang, Meng; Zhang, Dan
Abstract: This paper is concerned with the problem of dissipative output feedback tracking control for Markov jump systems under compensation scheme. The measured output of the system is assumed to be dropped in a probabilistic way before being transmitted to the controller. By virtue of the single exponential smoothing technique, a novel compensation strategy is proposed to help offset the impact of missing measurements. On this basis, an asynchronous output feedback tracking controller is designed to ensure the stochastic stability and strict dissipativity of the tracking error system. Then, sufficient conditions for the existence of the controller are derived via the mode-dependent and fuzzy-basis-dependent Lyapunov function. Finally, two practical examples are provided to illustrate the validity and applicability of the developed approach.